Polymer action on alkali-silica reaction: further research - Feiteira , J. (2012)
Polymer modification of mortar and concrete can lead to improved transport and mechanical properties and thus its potential for an inhibiting effect on ASR or on resulting damage was investigated. An accelerated mortar bar test in a NaOH solution bath at 80 ºC had already been established as inadequate to assess the behaviour of polymer-cement mortars (PCMs) under ASR, but compared to that of an unmodified mortar, the cement paste of PCMs had shown a higher resistance to microcracking resulting from ASR. In the present study, unmodified and styrene-butadiene and acrylic-styrene modified mortar bars were subjected to a moist 38 ºC environment and their Na2Oeq content previously raised to 1.25%. These test conditions promoted ASR development more consistently between mortars with significant differences in moisture transport properties. It was confirmed that despite the previously observed higher resistance to damage resulting from ASR, higher expansion is expected in PCMs compared to unmodified mortar. Even though a strong correlation was observed between expansion and the volume of open, interconnected porosity, it’s likely that closed porosity and significant differences in elastic modulus between PCMs and unmodified mortar are also responsible for the higher expansion of PCMs.